2005
DOI: 10.1148/radiol.2353040571
|View full text |Cite
|
Sign up to set email alerts
|

CT Sign of Brain Swelling without Concomitant Parenchymal Hypoattenuation: Comparison with Diffusion- and Perfusion-weighted MR Imaging

Abstract: The CT sign of brain swelling without concomitant parenchymal hypoattenuation in patients with acute cerebral ischemia does not represent severe ischemic damage and may suggest ischemic penumbral or oligemic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 27 publications
3
53
2
1
Order By: Relevance
“…19,20 However, other studies demonstrated that SE does not necessarily mean severe ischemic injury, especially if parenchymal hypoattenuation is absent. 1,21,22 An important limitation of noncontrast CT studies with respect to SE is poor agreement in distinguishing and estimating SE, even among experienced clinicians. 5,6,22 By contrast, the intraobserver and interobserver agreements were excellent in this study.…”
Section: Se On Flair Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, other studies demonstrated that SE does not necessarily mean severe ischemic injury, especially if parenchymal hypoattenuation is absent. 1,21,22 An important limitation of noncontrast CT studies with respect to SE is poor agreement in distinguishing and estimating SE, even among experienced clinicians. 5,6,22 By contrast, the intraobserver and interobserver agreements were excellent in this study.…”
Section: Se On Flair Mrimentioning
confidence: 99%
“…1 The EIC correlate with baseline stroke severity. 2 In addition, there is a trend of reduced risk and increased benefit to thrombolysis if the EIC on baseline CT are not extensive.…”
mentioning
confidence: 99%
“…29,30 Whereas loss of gray-white differentiation is consistent with infarction, 31 cerebral swelling may be intermixed, extending the apparent boundary of infarct. Cerebral swelling is associated with a variable and lower stroke risk 32 and may account for overestimation of initial infarct size on NCCT. Use of ASPECTS on CTA signal intensity allows easier detection of the infarct extent and provides additional information.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients were managed conservatively (only 2 IAT), and only 35% to 50% had lack of infarct within the ISE territory on follow-up imaging. 4,5 The frequency of ISE in our report compares favorably (7.4%), despite including only patients with confirmed large vessel occlusion. The CT perfusion patterns of our patients are comparable.…”
Section: Discussionmentioning
confidence: 43%
“…2,3 Sulcal effacement on NCCT and concomitant preservation of the underlying gray-white matter junction (isolated sulcal effacement [ISE]) may not represent cytotoxic edema. 1,4,5 We aimed to evaluate the frequency and significance of ISE in patients with large vessel occlusion acute ischemic stroke (AIS) undergoing intra-arterial therapy (IAT).…”
mentioning
confidence: 99%